Perfil epidemiológico da doença de chagas na região norte do Brasil entre os anos de 2019 e 2020 - PINTO, Jean Carlo Trindade (2023)
The objective of this research was to identify the epidemiological profile and analyze the occurrence of Chagas disease in the northern region of Brazil between 2019 and 2020. This is a retrospective, cross-sectional, quantitative and analytical study, using data provided by the DATASUS/MS system, and analyzed by Microsoft Office Excel 2016 and Biostat 5.3 software. In the north region, 502 notified cases of Acute Chagas Disease (DCA) were found in the analyzed period, with prevalence in the age group from 20 to 59 years old (n=317), male (57.57%), brown race/color (84.46 %) and higher occurrence in rural areas (n=1740) than in urban areas (n=145). The predominant mode of infection was oral contamination (87.85%) and the site of infection was at home (n=347). The state of Pará had a higher incidence of cases between 2019 and 2020 (n=397), mainly in the Tocantins health region (31.67%), and it was highlighted that the greater the number of cases of the disease, the lower the state's HDI. It is concluded that the North Region concentrates almost all ACD cases in the country, mainly the state of Pará, and this data has a direct correlation with the living conditions of the population and regional characteristics.